Hexagonal zinc oxide nanoparticles: a novel approach to combat multidrug-resistant Enterococcus faecalis biofilms in feline urinary tract infections - Sewid, Alaa H.; Sharaf, Mohamed; El-Demerdash, Azza S.; Ragab, Sherif M.; Al-Otibi, Fatimah O.; Taha Yassin, Mohamed; Liu, Chen-Guang (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionEnterococcus faecalis, a common inhabitant of the feline gastrointestinal tract, has emerged as a significant pathogen causing urinary tract infections (UTIs) in domestic cats. The rise of multidrug-resistant E. faecalis strains and their propensity to form biofilms pose significant challenges in treatment. This study investigated the antibacterial and antibiofilm activities of hexagonal zinc oxide nanoparticles (ZnONPs) alone and in combination with streptomycin and Moringa oleifera leaf extract (MOLe) against multidrug-resistant E. faecalis isolates from feline UTIs.MethodsAntimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Biofilm formation was assessed using the crystal violet assay, and biofilm-associated genes (sprE, gelE, fsrABC) were detected by PCR. ZnONPs, Str/ZnONPs (streptomycin-loaded ZnONPs), and Str/MOLe@ZnONPs (streptomycin and MOLe-loaded ZnONPs) were characterized using FTIR, DLS, TEM, and SEM. The antibacterial and antibiofilm activities of the synthesized nanoparticles were evaluated through time-kill assays, well diffusion assays, and gene expression analysis.ResultsA high prevalence of multidrug resistance was observed among the E. faecalis isolates, with significant resistance to ampicillin, vancomycin, and streptomycin. Characterization studies revealed the successful encapsulation of streptomycin and MOLe within the ZnONPs.In vitro assays demonstrated that Str/MOLe@ZnONPs exhibited potent antibacterial and antibiofilm activities against the tested E. faecalis strains, significantly reducing bacterial growth and biofilm formation.DiscussionThe emergence of multidrug-resistant E. faecalis strains necessitates the development of novel therapeutic strategies. This study demonstrates the promising potential of ZnONPs, particularly those loaded with streptomycin and MOLe, in combating biofilm-forming E. faecalis. The synergistic effects of the combined formulation may offer a novel approach to overcome antibiotic resistance and improve the treatment outcomes of E. faecalis UTIs in domestic cats.